Marketing Management of Islamic Educational Institutions: Manajemen Pemasaran Lembaga Pendidikan Islam - Ilahi, Farid Kurnia; Taufiqurrahman, Taufiqurrahman (Indonesian Journal of Education Methods Development, 2023)
Good marketing management is one of the factors to attract new prospective students. The purpose of this study is to describe the marketing management of educational institutions and to describe the factors that hinder and support the implementation of marketing in SMP Al Islamiyah Putat. This research is a qualitative research with research subjects including the principal, coordinator or person in charge of the school, teachers, and the community environment of SMP Al-Islamiyah Putat. From the research conducted, it was found that (1) Marketing planning is based on the school's vision and mission with modifications according to field conditions, (2) Organization has been running as expected under the leadership of the Principal who collaborates with stakeholders, (3) The movement process is based on the vision and mission which is strengthened by "excellent extra-curricular activities" are offered by schools through promotions on social media, brochures, and banners, (4) Marketing monitoring and evaluation is carried out every mid-semester at the beginning of the school year. Evaluation is carried out on the running of the programs offered and evaluates the potential of what programs already exist in schools that can be used as other keys in school marketing activities, (5) obstacles faced include the lack of budget to carry out promotional activities, lack of educators to doing marketing planning, and the lack of website utilization, and (6) supporting the success of marketing is the strong cooperation between teachers, the costs offered are affordable with adequate facilities, and the support of zoning rules that are enforced and the good image of the school in the surrounding community.